The Impact of Reinforcement Sensitivity Theory on Aggressive Behavior - Parker, Kristy-Elizabeth M. (Journal of interpersonal violence, 2022)
Why some people, and not others, exhibit aggression remains unknown. Research points to certain personality traits being linked to either proactive or reactive aggression, or both. The current study attempts to address these gaps from the perspective of revised Reinforcement Sensitivity Theory (rRST). Using 146 participants, results revealed Behavioral Approach System (BAS)-Impulsivity and the Behavioral Inhibition System (BIS) predicted proactive and reactive aggression. Defensive Fight predicted reactive aggression. BAS-Impulsivity predicted proactive aggression partially mediated by Social Dominance Orientation. These findings suggest proactive and reactive aggression are motivated by a combination of anxiety and rapid, approach-motivational personality traits. This study provides further understanding of the specific relations between rRST and aggression, is integrated into the general aggression model, and has implications for treatment of aggressive individuals.